What Determines the Domestic Bias and Foreign Bias? Evidence from Mutual Fund Equity Allocations Worldwide - CHAN, KALOK; COVRIG, VICENTIU; NG, LILIAN (Journal of Finance, 2005)
ABSTRACT We examine how mutual funds from 26 developed and developing countries allocate their investment between domestic and foreign equity markets and what factors determine their asset allocations worldwide. We find robust evidence that these funds, in aggregate, allocate a disproportionately larger fraction of investment to domestic stocks. Results indicate that the stock market development and familiarity variables have significant, but asymmetric, effects on the domestic bias (domestic investors overweighting the local markets) and foreign bias (foreign investors under or overweighting the overseas markets), and that economic development, capital controls, and withholding tax variables have significant effects only on the foreign bias.